Vocabulary learning strategies via video watching among high and low proficiency groups of form 2 ESL students in SMK Lokman Hakim / Norhaslinda Muhamadin - Muhamadin, Norhaslinda (Faculty of Education, 2014)
Recently, the inclusion of multimedia has dominated the various teaching and learning practices of English as Second Language especially in terms of vocabulary acquisition (Harji, Woods & Alavi, 2010). This study intended to explore the Vocabulary Learning Strategies via Video Watching applied by the high and low proficiency groups of Form 2 students in SMK Lokman Hakim, Kota Tinggi, Johor. Guided by four research objectives and five research questions, this study employed a mixed-methods research design using both quantitative and qualitative approaches for data collection and analysis. There were 48 participants involved in the study: 26 were from high proficiency group and 22 were from low proficiency group. The findings revealed that firstly, the higher proficiency group was more positive towards English video watching as opposed to the low proficiency group. Second, the high proficiency group scored higher in their vocabulary test as compared to the low proficiency group. Third, high proficiency group tend to have higher mean score in the application of Vocabulary Learning Strategies via Video Watching than the low proficiency group when answering the vocabulary test. Fourth, the findings demonstrated that there was a significant difference of mean scores between the two groups in the vocabulary test. Fifth, there was also a significant difference of mean scores between the two groups in applying the Vocabulary Learning Strategies via Video Watching when answering the vocabulary test. Lastly, the qualitative findings tend to corroborate the fifth research question. It was found that the high proficiency students had applied other vocabulary learning strategies as stated in the questionnaire. Hence, discussion, pedagogical implications and recommendations for future research were presented to conclude the study.